2021
DOI: 10.3389/fcvm.2021.683216
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Disappearance of Coronary Anastomotic Aneurysm by Steroid Therapy in Takayasu Arteritis: Pseudorepair of Pseudoaneurysm?

Abstract: Background: Takayasu arteritis (TA) is a large vessel vasculitis of unknown etiology characterized by chronic inflammatory changes of the aorta and its major branches. Complications such as anastomotic aneurysm and valve detachment have been reported in active TA patients who received aortic valve replacement and graft replacement of aorta.Case Summary:A 61-year-old man with a history of emergency aortic valve replacement and patch closure of the noncoronary sinus of Valsalva due to acute heart failure induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Multiple reports detailing cases of delayed postoperative complications suggest reentry into the active inflammation phase of TA as an underlying cause. These include a case of delayed dehiscence 6 and a pseudoaneurysm in the coronary button following aortic root replacements, 7 with the authors of one report making the argument for lifelong monitoring of inflammation following surgery for some TA patients. 8 In the present case, pseudoaneurysm formation was not observed during follow-up because of the horizontal mattress sutures from the outside to the inside of the aortic root and appropriate inflammation control.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports detailing cases of delayed postoperative complications suggest reentry into the active inflammation phase of TA as an underlying cause. These include a case of delayed dehiscence 6 and a pseudoaneurysm in the coronary button following aortic root replacements, 7 with the authors of one report making the argument for lifelong monitoring of inflammation following surgery for some TA patients. 8 In the present case, pseudoaneurysm formation was not observed during follow-up because of the horizontal mattress sutures from the outside to the inside of the aortic root and appropriate inflammation control.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppressive treatment with glucocorticoid is suggested for the prevention of these complications [ 25 ]. There is also a report of successful resolution of anastomotic pseudoaneurysm developed after aortic graft replacement for aortic aneurysm due to Behçet’s aortitis with glucocorticoid treatment [ 26 ]. This observation suggested that immune-mediated inflammation can cause detachment of the implanted prosthetic valve or graft, or anastomotic aneurysm formation.…”
Section: Discussionmentioning
confidence: 99%